2021
DOI: 10.7554/elife.70333
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone screen testing, a novel pre-diagnostic method to identify SARS-CoV-2 infectious individuals

Abstract: The COVID-19 pandemic will likely take years to control globally, and constant epidemic surveillance will be required to limit the spread of SARS-CoV-2, especially considering the emergence of new variants that could hamper the effect of vaccination efforts. We developed a simple and robust - Phone Screen Testing (PoST) - method to detect positive SARS-CoV-2 individuals by RT-PCR testing of smartphone screen swab samples. We show that 81.3-100% of individuals with high-viral load SARS-CoV-2 nasopharyngeal posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…We envision that this approach, with proper safety precautions, could be used for home-based testing, as demonstrated by others. 3 , 4 , 19 , 21 The portable multiplexing detection prototype was built with two wavelengths in the optical system: a LED working at 490/26 nm excitation for FITC, and a second LED working at 625/17 nm with the same length of impulse for Cy5 excitation. A combination of reporter pairs could be used for this portable device such as SYTO TM 62 using Cy5 channel for tracking amplification and FRET-based FAM reporter using the FITC channel for detection of BrCas12b trans-cleavage activity, or the SYTO TM 9 and Cy5 reporter pair for the opposite channels.…”
Section: Resultsmentioning
confidence: 99%
“…We envision that this approach, with proper safety precautions, could be used for home-based testing, as demonstrated by others. 3 , 4 , 19 , 21 The portable multiplexing detection prototype was built with two wavelengths in the optical system: a LED working at 490/26 nm excitation for FITC, and a second LED working at 625/17 nm with the same length of impulse for Cy5 excitation. A combination of reporter pairs could be used for this portable device such as SYTO TM 62 using Cy5 channel for tracking amplification and FRET-based FAM reporter using the FITC channel for detection of BrCas12b trans-cleavage activity, or the SYTO TM 9 and Cy5 reporter pair for the opposite channels.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, saliva is a highly desirable specimen, which can also be easily collected. Young et al [39] demonstrated that smartphone screen swab samples could also be used for detecting positive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…2f). We envision that this approach, with proper safety precautions, could be used for home-based testing, as demonstrated by others 3,4,13,20 . The portable multiplexing detection prototype was built with two wavelengths in the optical system: a LED working at 490/26 nm excitation for FITC, and a second LED working at 625/17 nm with the same length of impulse for Cy5 excitation.…”
Section: Mainmentioning
confidence: 90%